NEW LITERACY AND DATA-FUTURE IN EDUCATION: ADVANCED TECHNOLOGY SMART BIG-DATA - Fiofanova, Olga (Revista Inclusiones, 2020)
The content of the study is presented: how the countries of the world are developing digital educational platforms, digital educational data services, and technologies for managing the development of education based on smart data. It reveals: how national education systems are revising educational approaches in order to create opportunities to develop new literacy and competencies of the future. It is presented: how the development of big-data, smart-data, block-chain technologies will lead to a change in assessment tools, regulations for converting educational results at different levels of education and in different forms of education (formal and non-formal education). It is described: how the countries of the world implement models of educational data analysis in education based on the development of digital platforms and services for the analysis of educational data and educational statistics.